Education Level and Income Tax Compliance Amongst Small and Medium Enterprises in Soroti, Uganda - Otai Isaac Peter (Review of International Economic, Taxation, and Regulations, 2025)
Tax compliance persists as a salient challenge across numerous developing economies, including Uganda, where an array of socio-demographic determinants conditions taxpayer comportment. This inquiry endeavors to interrogate the effect of taxpayers’ educational attainment on income tax compliance within Soroti District, Uganda. It utilizes both descriptive and explanatory research paradigms, drawing upon data elicited from 384 randomly selected proprietors of sole proprietorship SMEs via structured questionnaires, which were subsequently subjected to inferential statistical scrutiny. The findings disclose that educational attainment demonstrates a statistically substantive association with income tax compliance, particularly with respect to the punctual lodgment of tax returns and the expeditious settlement of income tax liabilities. This study augments extant literature by redressing an evident gaps, given that the salience of education as a demographic determinant of tax compliance remains comparatively underexamined within the Ugandan milieu. Consequently, it recommends that policymakers duly incorporate taxpayers’ educational profiles when devising interventions aimed at bolstering individual income tax compliance.